PENGARUH RASIO KESEHATAN BANK TERHADAP RETURN ONASSET BANK BUKU EMPAT DI INDONESIA - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2017)
The purpose of this study was to determine the effect of the Bank Against Ratio Return on Assets (ROA) Bank Book Four in Indonesia. The population in this study are all banks included in the book category 4 by 4 conventional commercial banks. The sample is determined by purposive sampling with the aim to obtain a sample in accordance with predetermined criteria. The sample in this research there are four conventional commercial banks. The analytical tool used multiple linear regression. The results of analysis show that the Operating Expense to Operating Income (ROA), Net Interest Margin (NIM), Net Interesrt Margin (NIM), Capital Adequacy Ratio (CAR), Loans to Deposit Ratio (LDR) significantly affects the Return on Assets (ROA) the Bank BOOK 4 in Indonesia. Partially (respectively) can be concluded Operating Expense to Operating Income (ROA) Against the Return On Asset (ROA) were significant at 4 BOOK Bank in Indonesia. Partially (respectively) can be concluded there is a significant effect NIM (X2) to ROA (Y) on the Bank BOOK 4 in Indonesia. Partially (respectively) we can conclude that there is significant influence CAR (X1) Return on Equity (Y) on the Bank BOOK 4 in Indonesia.Secara partial (respective) we can conclude that there is significant influence LDR (X4) against ROA (Y) on the Bank BOOK 4 in Indonesia. Operating Expense to Operating Income (ROA), Net Interest Margin (NIM), Net Interesrt Margin (NIM), Capital Adequacy Ratio (CAR), Loans to Deposit Ratio (LDR) has a correlation (R) high Return on Assets ( ROA) at 4 BOOKS Bank in Indonesia. Then the coefficient of determination (adjusted R2) explained that the Operating Expenses to Operating Income (ROA), Net Interest Margin (NIM), Net Interesrt Margin (NIM), Capital Adequacy Ratio (CAR), Loans to Deposit Ratio (LDR) may affect the return on assets (ROA) at Bank BOOK 4.